Growth, condition factor and gonadosomatic index of Asian Seabass (Lates calcarifer) in the coastal water of Pahang - Rahman, Mohammad Mustafizur; Samad, Amira Farzana; Yunus, Kamaruzzaman (2014)
Asian seabass (Lates calcarifer) is a very important target fish for fisherman because it enjoys very high consumer preference and market price. Presently, the total capture production of this fish is decreasing rapidly in Malaysia due to decreasing wild stock. However, necessary information about Asian seabass population in Pahang coastal water is lacking for the proper management of this fish. Therefore, a study was conducted to understand some basic characteristics (growth, condition factor and spawning) of Asian seabass population in Pahang coastal water. Fish samples were collected from different region of Pahang for a period of one year. The growth coefficient was calculated by regression analysis using the logarithmic transformed equation logW = loga + b.logL derived from W = a.Lb (where, W = body weight; L = total length). The condition factor (K) was calculated for each individual fish according to the formula K = (W/L3) * 100. The gonadosomatic index (GSI) was calculated using the formula, GSI (%) = (GW/W) * 100 (where, GW = gonad weight). The results showed that the growth coefficient varied from 1.6034 (end of July) and 3.4264 (November). Negative allometric growth was observed in Asian seabass in all samplings except in November and in the middle of July. An isometric growth of Asian seabass was observed in the middle of July (W = 0.0139L2.9962, R2 = 0.9979, P<0.01) and a positive allometric growth was observed in November (W = 0.002L3.4264, R2 = 0.9974, P<0.05). The condition factor of Asian seabass ranged from 1.195 to 1.505. The significantly lowest mean condition factor was found in the November and the highest was observed in the August. Overall high value of condition factor was observed in smaller fish (less than 46 cm total length) while low value of condition factor was observed in medium size fish (56-70 cm total length). The lowest gonadosomatic index of Asian seabass was observed in October and November. Overall gonadosomatic index of Asian seabass was higher from May to August with a very few exception. Based on this study, the spawning season of Asian seabass in Pahang coastal water might be from May to August but more research is needed to confirm this. The information of this study would be used for both applied and basic use for the management of wild Asian seabass stock in the coastal water of Pahang.